NOUN NUMBERS IN ARABIC: CLASSIFICATION AND FORMATION OF MUFRAD, MUNFASIL, AND JAM (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the category of number, one of the grammatical categories of the Arabic language. The article analyzes the three number categories in Arabic—singular ( مفر د – mufrad), dual (مثنى – musanna), and plural (جمع – jamʿ)—based on their definitions, formation rules, and examples. In particular, the types of plural—broken plural (jam' taksir) and sound plural (jam' salim)—and the division of the sound plural into masculine and feminine forms are highlighted separately. The original Arabic definitions and their Uzbek explanations presented in the article help to gain a deeper understanding of the topic. This article can serve as a practical guide for students of Arabic and specialists in the field of linguistics.